The development of practice standards for graduates of Australian critical care nurse education: the AusDACE study - Gill, Fenella Jane (Curtin University, 2014)
A mixed-method design was used to develop national practice standards for graduates of Australian critical care nurse education and a clinical assessment tool to measure graduate practice. Critical care nursing stakeholders, patients and families informed the multi-phase process. The expected graduate level of practice was identified as the safe practitioner who can care for most critically ill patients, but not as team leader. These findings provide greater consistency in determining graduate practice outcomes.